Humanitarian Intervention in the Long Nineteenth Century Setting the Precedent - Heraclides, Alexis (Humanitarianism: Key Debates and New Approaches, 2015)
This book is a comprehensive presentation of humanitarian intervention in theory and practice during the course of the nineteenth century. Through four case studies, it sheds new light on the international law debate and the political theory on intervention, linking them to ongoing issues, and paying particular attention to the lesser known Russian dimension.The book begins by tracing the genealogy of the idea of humanitarian intervention to the Renaissance, evaluating the Eurocentric gaze of the civilisation-barbarity dichotomy, and elucidates the international legal arguments of both advocates and opponents of intervention, as well as the views of major political theorists. It then goes on to examine four cases as humanitarian interventions: the Greek War of Independence (1821-31), the Lebanon and Syria (1860-61), the Bulgarian atrocities (1876-78), and the U.S. intervention in Cuba (1895-98).